2015
DOI: 10.1088/0029-5515/55/5/053030
|View full text |Cite
|
Sign up to set email alerts
|

Advances in stellarator gyrokinetics

Abstract: Recent progress in the gyrokinetic theory of stellarator microinstabilities and turbulence simulations is summarised. The simulations have been carried out using two different gyrokinetic codes, the global particle-in-cell code EUTERPE and the continuum code GENE, which operates in the geometry of a flux tube or a flux surface but is local in the radial direction. Ion-temperature-gradient (ITG) and trapped-electron modes are studied and compared with their counterparts in axisymmetric tokamak geometry. Several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 22 publications
3
76
0
Order By: Relevance
“…On the other hand, if the electrons are in a ground state, they act to stabilise any ion-driven instability and one would expect that the available energy is relatively small. Gyrokinetic simulations of turbulence in approximately maximum-J stellarator configurations do indeed suggest that the transport under these conditions is up to an order of magnitude smaller than in a typical tokamak (Helander et al 2015).…”
Section: P Helandermentioning
confidence: 86%
“…On the other hand, if the electrons are in a ground state, they act to stabilise any ion-driven instability and one would expect that the available energy is relatively small. Gyrokinetic simulations of turbulence in approximately maximum-J stellarator configurations do indeed suggest that the transport under these conditions is up to an order of magnitude smaller than in a typical tokamak (Helander et al 2015).…”
Section: P Helandermentioning
confidence: 86%
“…Moreover, in quasi-isodynamic configurations with the socalled 'maximum-J' property (the parallel adiabatic invariant J attains its maximum on the magnetic field axis, while monotonically decreasing towards the edge), it can be analytically shown that collisionless TEMs are stable over a large parameter range [9]. An electron displaced by the density gradient would need to gain energy in order to conserve J (for ∂J/∂r < 0) thus tapping energy from the instability.…”
Section: Turbulence In Advanced Stellaratorsmentioning
confidence: 99%
“…A very interesting question is how neoclassical optimization of ε eff affects turbulent transport. 3-D calculations of ion-temperature-gradient-driven turbulence suggest a critical gradient similar to tokamaks, but with much reduced temperature profile stiffness [20], [21]. An interesting question, which the W7-X results will have to answer, is whether an H-mode transport barrier [22] at the plasma edge will be required to achieve sufficiently good confinement.…”
Section: Development Of Integrated Steady-state Plasmas (Op2)mentioning
confidence: 99%